English Teachers’ Perception and Use of Technology During the COVID-19 Pandemic - Hafizhatu Nadia; Yansyah Yansyah; Ahmad Kailani; Dina Rafidiyah (Universitas Muhammadiyah Mataram, 2021)
The inclusion of information and communication technology is a requirement in today’s education. During the COVID-19 outbreak, this necessity becomes more significant since we need to move from face-to-face to online classrooms. This article aims to explore English teachers’ perception and use of technology during the COVID-19 pandemic. Twenty-two English teachers in South Kalimantan voluntarily joined this research. Questionnaire and interview are two main instruments to collect the data. The questionnaire explored their perceptions on how technology helped them in improving the learning quality during remote teaching. Then, the interview is intended to deepen the data regarding the information given by the participants. The findings reveal that most English teacher's had positive attitudes toward the use of technology to improve the quality of learning. In addition, the condition of COVID-19 made them learn to use various digital tools to teach English. Some challenges and recommendations are discussed.